Navigating Inflationary Stress Through Adaptive Investment Strategies - Amulya Gudimella; Anikesh Dulgande; Anushtha Choudhary; Murari Konduri (Involvement International Journal of Business, 2025)
Inflation is a central determinant of stock market behavior, yet its effects vary across economies and periods. While moderate inflation may sustain growth, high inflation combined with systemic shocks can destabilize markets and erode investor confidence. This study adopted a comparative analysis of historical data from the United States and India between 2001 and 2023, focusing on inflation trends, stock market indices (S&P 500 and NIFTY), and policy responses. The analysis combined quantitative market data with qualitative assessments of policy interventions and sectoral performance. Findings reveal that moderate inflation of 2–4% supported consistent S&P 500 growth from 2010 to 2019, whereas extreme inflation, 12.7% in India (2013) and 9.1% in the US (2022) led to market volatility and portfolio reallocation. Severe contractions were observed during crises, including a -51.79% decline in India’s NIFTY (2009) and a -38.49% fall in the US S&P 500 (2008). Defensive sectors such as utilities and consumer staples provided stability, while technology and growth sectors were highly vulnerable. Policy responses strongly influenced market outcomes. Gradual interventions, such as US interest rate hikes in 2022–2023, moderated risks, while abrupt reforms like India’s GST in 2017 intensified instability. Diversification, macroeconomic monitoring, AI-driven predictive analytics, and ESG integration emerged as key strategies to mitigate inflationary stress. The results highlight that inflation’s impact is context-dependent and amplified by crises, but adaptive strategies can strengthen resilience. Limitations stem from reliance on historical data, suggesting future research should explore AI forecasting and ESG frameworks across broader global markets.